1963
DOI: 10.1111/j.1365-2621.1963.tb01680.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Taste Intensities of Selected Sugars and Organic Acidsa

Abstract: A highly trained taste panel was used to establish the concentrations of fructose, glucose, and lactose equivalent in sweetness to sucrose at threshold and suprathreshold concentrations.The same panel established the sourness of lactic, tartaric, and acetic acids equivalent to that of' citric acid at threshold and snprathresholdconcentrations.There was no relation between pH, total acidity, and relative sourness. Results obtained from determinations made in water solutions agreed favorably with values reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
3

Year Published

1969
1969
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(93 citation statements)
references
References 11 publications
4
86
0
3
Order By: Relevance
“…Methodology among studies varied considerably. Yamaguchi et al (1970) used a large taste panel (25 or 50 subjects), the method of constant stimuli as thll psychophysical technique, and probit analysis for statistical interpretation; Pangborn (1963) also used the method of constant stimuli, but with 12 subjects and linear regression for statistical analysis; Cameron (Note 1) used a Figure 6. Comparison of the sweetness-matching function for sucrose and fructose predicted by category scaling in the present study (curve), and the results of four different studies in which sweetness matching was actually the task used-open squares (Cameron,Note 1), open circles (Dahlberg & Penczek, Note 2), triangles (Pangborn, 1963), and inverted triangles (Yamaguchi et al, 1970 Sucrose concentration (0/0 w/vl and fructose using magnitude estimation, Cardello, Hunt, and Mann (1979) also found fructose to be sweeter than sucrose, but with the sweetness differential diminishing at high concentration.…”
Section: Comparison With Sweetness-matching Studiesmentioning
confidence: 99%
“…Methodology among studies varied considerably. Yamaguchi et al (1970) used a large taste panel (25 or 50 subjects), the method of constant stimuli as thll psychophysical technique, and probit analysis for statistical interpretation; Pangborn (1963) also used the method of constant stimuli, but with 12 subjects and linear regression for statistical analysis; Cameron (Note 1) used a Figure 6. Comparison of the sweetness-matching function for sucrose and fructose predicted by category scaling in the present study (curve), and the results of four different studies in which sweetness matching was actually the task used-open squares (Cameron,Note 1), open circles (Dahlberg & Penczek, Note 2), triangles (Pangborn, 1963), and inverted triangles (Yamaguchi et al, 1970 Sucrose concentration (0/0 w/vl and fructose using magnitude estimation, Cardello, Hunt, and Mann (1979) also found fructose to be sweeter than sucrose, but with the sweetness differential diminishing at high concentration.…”
Section: Comparison With Sweetness-matching Studiesmentioning
confidence: 99%
“…Pangborn (1963) found that in water solutions fructose was rated sweeter than sucrose (on a weight basis), whereas in viscous pear nectar the order was reversed. On the other hand, Skramlik (1926) demonstrated that the intensity of taste was consistently lower in paraffin oil than in water.…”
mentioning
confidence: 99%
“…The problem of the interaction between pairs of taste qualities has been dealt with in the series of reports by Pangborn and her associates (Pangborn, 1960(Pangborn, , 1961(Pangborn, , 1962(Pangborn, , 1963(Pangborn, , 1964Pangborn, Ough, & Chrisp, 1964;Pangborn & Trabue, 1964); by Kamenetzky and Pilgrim (1958); and in an entirely different approach by Bekesy (1964). The picture is not simple, and the same may be said of the present results.…”
Section: Interactionsmentioning
confidence: 69%